Time to take a risk effect of risk aversion and time preference on decision to borrow and creditor choice - Gloria, Rella Denisse S. (School of Economics, University of the Philippines Diliman, 2019)
This study examines the marginal effects of risk aversion and time preference on the decision to borrow and in the selection of creditor. Using the Consumer Finance Survey (CFS) 2014, a nationwide quadrennial survey administered by BSP, we inspect the probability of having a loan and having a loan from a formal source. To address probable selection bias, we implemented a two_step heck probit on the CFS. We find that risk averse individuals are more likely to not hold a loan, and those with loans are disinclined to borrow from formal sources of credit. Moreover, time preference does not have any significant effect on credit participation nor on the selection of creditor.